2010
DOI: 10.18438/b8vg9r
|View full text |Cite
|
Sign up to set email alerts
|

Course-Integrated Learning Outcomes for Library Database Searching: Three Assessment Points on the Path of Evidence

Abstract: Commons-Attribution-Noncommercial-Share Alike License 2.5 Canada (http://creativecommons.org/licenses/bync-sa/2.5/ca/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly attributed, not used for commercial purposes, and, if transformed, the resulting work is redistributed under the same or similar license to this one. AbstractObjective -This study aims to assess student learning with respect to basic database searching at three different points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The majority of students are able to use, at least in part, what was taught in the ILI session. While this is encouraging, Cmor, Chan, and Kong (2010) found that while the majority of students could complete information literacy-related exercises in ILI sessions, few were able to demonstrate the ability to use new tools and search strategies or incorporate new knowledge into projects.…”
Section: How Students Are Searchingmentioning
confidence: 92%
See 1 more Smart Citation
“…The majority of students are able to use, at least in part, what was taught in the ILI session. While this is encouraging, Cmor, Chan, and Kong (2010) found that while the majority of students could complete information literacy-related exercises in ILI sessions, few were able to demonstrate the ability to use new tools and search strategies or incorporate new knowledge into projects.…”
Section: How Students Are Searchingmentioning
confidence: 92%
“…While students demonstrate that they can use what was taught in class, it is unknown if students can take that learning beyond the classroom and some research (e.g., Cmor et al, 2010) suggests it is doubtful. In addition, it is difficult to know whether students can extrapolate their learning in class to a greater understanding of research as a process.…”
Section: Implications For Future Practice and Researchmentioning
confidence: 99%
“…Cmor, Chan, and Kong examined literature searching exercises and viewed oral presentations in which students described their search strategies that were recorded immediately post-training and again two weeks after instruction [42]. Content analysis showed that during the 2 weeks immediately following instruction, students reverted to ineffective searching behaviors.…”
Section: Timing Matters: Formative and Summative Evaluationmentioning
confidence: 99%
“…A question raised by the lack of precision in using the phrases "ethnographic studies" and "ethnographic methods" is the categorization of studies as ethnographies when the researchers never identified their studies as ethnographies or their methods as ethnographic (Briden & Marshall, 2010;Cmor, Chan, & Kong, 2010). More information about the definitions of ethnography found in the literature would have been useful, especially those definitions that were "induced indirectly" from the literature studies (p. 84).…”
Section: Commentarymentioning
confidence: 99%